Comparisons of interactive and interactional metadiscourse among undergraduates / Masliza Mat Zali ... [et al.] - Mat Zali, Masliza; Mohamad, Razita; Setia, Roszainora; Raja Baniamin, Raja Mariam; Mohd Razlan, Razifa (Universiti Teknologi MARA, 2020)
Interactive and interactional metadiscourse are linguistic features used to maintain the coherence in essays. It involved a one-way interaction between the writer and reader, thus a challenge for Second Language (L2) learners to write effectively and comprehensively. A study is done on how the L2 learners produced the metadiscourse features and the usage is compared. A corpus of 200 evaluative essays by UiTM undergraduate students from computer science and business administration courses is analysed based on Hyland’s (2005) framework. The purpose is to find out the amount and types of metadiscourse used and whether students from different course groups make any differences in their choices. The analysis revealed that students in both courses produced more interactive than interactional metadiscourse. The most prominent feature is Self-mention and the least is Attitude Markers. The same prominent feature for both courses is Transition Markers. The business administration course shows the least feature in Evidentials, whereas Frame Markers in computer science. These are evidence as to the importance of metadiscourse in students’ academic writings and awareness is shown in its usage. This could lead to a proposition for a metadiscourse writing comparison between secondary schools and universities to gain fascinating outcomes.